(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
"Design thinking" (DТ) is an innovative concept for making and implementing new business solutions (products, services, processes), contributing to an increase in their quality according to the expectations and requirements of their users. His methodology involves thorough research and understanding of stakeholders, as well as qualitative changes to the outcome with rapid implementation of corrective actions. "Design thinking" is also a modern tool for achieving innovation through creative co-creation of the final solution by working in teams together with customers. Because of this, this methodology is increasingly used in making management decisions of a different nature, especially in product management – the area in which the goal is to create quality product innovations. In connection with the practical interpretation of the DТ methodology in product management, in making operational management decisions related to innovation and modelling of innovative products, the authors also created a short-term training course program for specialists in the field of standardization and quality management, members on "Club 9000". The purpose of the training is to present the methodology of DТ, its algorithm and the possibilities of its use as an innovative tool in the process of creating new products while minimizing risk. At the same time, it is aimed to support through interactive training the building of practical skills for work, using tools from the specially created Manual for the application of DТ in modelling innovative products in a specific sector (Woodworking and furniture industry).